The Model for Predicting Self-Harming Behaviors Based on Cognitive Emotion Regulation Strategies and Emotional Distress Tolerance in Adolescents Visiting Harm Reduction Centers in Tehran: The Mediating Role of Internalized Shame - Abbasi Abrazgah, Mojgan; Bostansara, Maryam; Aghighi Ravan, Fatemeh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to predict self-harming behaviors based on cognitive emotion regulation strategies and emotional distress tolerance, with the mediating role of internalized shame in adolescents visiting harm reduction centers in Tehran.Methods: The research employed a descriptive correlational design. The statistical population included adolescents aged 14 to 18 who attended drop-in harm reduction centers in District 12 of Tehran (Shush-Harandi neighborhood) during the first four months of 2022. A total of 300 participants were selected using purposive sampling. The research tools included the Self-Injury Questionnaire (Sansone et al., 1998), the Cognitive Emotion Regulation Questionnaire (Garnefski et al., 2001), the Distress Tolerance Scale (Simons & Gaher, 2005), and the Internalized Shame Scale (Cook, 1993). Data were analyzed using structural equation modeling and AMOS24 software.Findings: The results indicated a relationship between cognitive emotion regulation strategies (-0.39), emotional distress tolerance (-0.41), internalized shame (0.36), and self-harming behaviors (P < 0.01). Furthermore, internalized shame mediated the relationship between cognitive emotion regulation strategies (B = 0.52) and emotional distress tolerance (B = 0.45) with self-harming behaviors in adolescents (P < 0.01).Conclusion: Based on these findings, it can be concluded that since internalized shame mediates the relationship between cognitive emotion regulation strategies and emotional distress tolerance with self-harming behaviors, focusing on factors influencing these behaviors can help reduce the risks associated with this developmental period.